THE EFFECT OF THE CLASSROOM CLIMATE, STUDENTS’ ATTITUDES, AND PERCEPTIONS ON MATH TOWARD THE ASSOCIATION MATERIAL LEARNING OUTCOMES THROUGH STUDENTS’ MOTIVATION OF CLASS VII SMP IN THE DISTRICT OF KOLAKA - Made Subawo (JME (Journal of Mathematics Education), 2016)
The Influence of The Classroom Climate, Students Attitude and Perception in Mathematics toward Mathematics Learning Outcomes through Learning Motivation of Class VII Student at SMPN in Kolaka. This research aimed to discover the description and the influence of classroom climate, student’s attitude and perception in mathematics toward the association material learning outcome through learning motivation of class VII students at SMPN in Kolaka. This research was causality ex-post facto research. The sample and population of this research was the student of class VII of SMPN in Kolaka subdistrict with the total of 227 students in academic year of 2013/2014 chosen by using proportional cluster random sampling. The instruments of this research were: 1) classroom climate scale, 2) the students’ attitude in mathematics scale, 3) the students’ perception in mathematics scale, 4) learning motivation scale, 5) the test of mathematics learning outcomes in class VII. The data was analyzed by descriptive statistic and path analysis. The result of the research showed that: 1) 227 students of class VII at SMPN in Kolaka had: classroom climate was in high category, the students’ attitude in mathematics was in high category, the students’ perception in Mathematics was in high category, learning motivation was in high category, and the cognitive learning outcomes was in high category; 2) there were positive and significant influence of the classroom climate toward the students’ outcome directly and or indirectly through the students’ learning motivation in mathematics ; 3) there were positive and significant influence of the students’ attitude in mathematics toward the students’ outcome directly and or indirectly through the students’ learning motivationin mathematics; 4) there were positive and significant influence of the students’ perception in mathematics toward the students’ outcome directly and or indirectly through the students’ learning motivation in mathematics; 5) there were positive and significant influence of the students’ learning motivation toward the students’ outcome directly and or indirectly through the students’ learning motivation in mathematics.